EFEKTIFITAS KOMPRES AIR HANGAT TERHADAP PENURUNAN NYERI SENDI PENDERITA GOUT ARTHRITIS - Siregar, Munawaroh; Dewi, Ari Pristiana; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Warm water compresses is the treatment that can be used to reduce the intensity of pain in people with gout arthritis. The purpose of this research is to identify effectiveness of warm water compresses on reducing of joint pain of gout arthritis patient using pre experiment (one group pre-test post test). Sample of this study is 17 people as warm water compresses group based on inclusion criteria using purposive sampling technique. The group of warm water compresses. were given intervention for 2 days consecutively. This research measured by NRS. The univariate analysis was conducted to show frequency distribution and bivariate analysis was conducted by Wilcoxon test. The statistic showed p value (0.000) < α (0.05), which means that there was no significant effectiveness warm water compresses on reducing of joint gout arthritis patient. Warm water compresses has similar characteristics in lowering the pain scale of gout arthritis patient, this compresses can be used as a reference when health education or family care in the community. Keyword: Gout Arthritis, Warm Water Compresses, Joint Pain